থংবোইগী মপা - Kamal Toijamba (Toijam Publications, 2015)
This book is a collection of short stories.
Thangboigee Mapa
Keywords: Manipuri; থংবোইগী মপা; Thangboigee Mapa; Short stories; Manipuri; Manipuri